PARTISIPASI MASYARAKAT DALAM PENGELOLAAN OBYEK WISATA ALAM AIR PANAS DAN AIR TERJUN DI DESA MANTIKOLE KECAMATAN DOLO BARAT KABUPATEN SIGI - Dg. Materru, Rahmah H. Abd. Hay (Katalogis, 2017)
The Reseach problems are (1) How are the roles of the local communityin the management of natural tourismobject, the spring and the waterfall, (2)How does the local community participate in the management, (3) How are the roles of the local government in the management of the tourism object. The research isqualitatif desciptive. The data were obtained from the observations, interviews, and questioners. The data were analyzed by using data reduction, data presentation, and verification.Â  The research involved 30 local residents near the tourism object and some informants including the local principals, the chairperson, the elders, the youth figures, the parking men, the guards, and the sellers. The result shows that the local community roles in managing the object are not maximum in some aspects such as economy, social, culture, law, and environmental regulation. Their participation is not maximum shown by their jobs in which they work only as the employee. In addition, the local government roles are not maximum because the accommodation and regulation are not well provided. Theirroles and their participation in managing thenatural tourismobject, the spring and the waterfall in Mantikole are not maximum in some aspects such as economy, social, culture, law, and environmental regulation. The local communityâ€™s participation is limited as workers around the area. The government roles are not maximum in providing some accommodations and regulations in that tourism object.